Fitting Time to First Birth Using Extended Cox Regression Model in Presence of Nonproportional Hazard (Dhaka University Journal of Science, 2015)
The Cox regression model, which is widely used for the analysis of factor effects with censored survival data, makes the assumption of constant hazard ratio. Different methods should be used to deal with non-proportionality of hazards when this assumption is violated. In this study, we use the Extended Cox regression model where time dependent covariate terms with fixed functions of time are considered. Time to first birth for the ever married women after marriage, taken from BDHS 2011 women data is fitted using Extended Cox regression model due to the failure of existence of proportionality assumption. This model performs well as expected compared to Cox regression model. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21764 Dhaka Univ. J. Sci. 63(1): 25-30, 2015 (January)